Rapid Assessment of Diverse Trichodermal Isolates of Indonesian Origin for Cellulase Production - Fahrurrozi, Fahrurrozi; Ratnakomala, Shanti; Lisdiyanti, Puspita; Anindyawati, Trisanti; Sukara, Endang (BRIN, 2010)
Trichoderma is a well-known candidate to be promoted as cellulase producer for the hidrolysis of lignocellulose that contain in woody biomass. The number of trichodermal isolates in our laboratory collected from diverse ecosystem types in Indonesia increases significantly during the last 5 years. It is our aim to assess the cultures for its ability in producing cellulase. Sixty-six trichodermal isolates used in this experiment are obtained from Biotechnology Culture Collection (BTCC), Research Center for Biotechnology, Indonesian Institute of Sciences (LIPI). The 31 isolates were isolated from District of Liwa (South Sumatra, Indonesia) and the 35 isolates from District of Maros (South Sulawesi, Indonesia). The isolates were screened qualitatively, 7 isolates from Liwa and 12 isolates from Maros showed cellulolytic activity. From the results of quantitative test, two strains (ID08-T004 and ID08-T63) showed the higher cellulolytic activity among the selected strains, 133.5 and 133.5 U/ml, respectively. These extracellular enzymes were characterized their temperature and pH optimum. The temperature optimum for both enzymes was the same, 50C, with activity 213.6 U/ml for enzyme extracted from ID08-T004 and 197.3 U/ml for enzyme from ID08-T0063. The pH optimum was pH 5 of ID08-T004 with activity 137.7 U/ml and pH 6 for ID08-T063 with activity 75.0 U/ml. The enzymes from ID08-T004 and ID08-T063 were stable in their temperature and pH optimal condition even after 90 minutes incubation with activity 179.0 U/ml and 86.7 U/ml, respectively. The enzyme stability was approximately 150 minutes for both enzymes in the temperature and pH optimum.